Flood Operation Pattern on Gated and Free-Flow Spillways of Tiu Suntuk Dam, West Sumbawa Regency - Supriyanto, Angga; Suharyanto, Suharyanto (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to assess the storage capacity and determine the effectiveness of gate operation in flood routing at Tiu Suntuk Dam. The analysis was conducted using the HEC-HMS hydrological model with a reservoir routing approach to simulate the relationship between inflow, outflow, and changes in reservoir water level (RWL) under various gate operation scenarios. The results from the supervision consultant indicate that the total storage capacity of the dam is 60.86 million m³, with an effective volume of 57.34 million m³ and a flood control storage of 13.51 million m³. Four gate operation scenarios were tested, combining fully open and closed conditions at initial water levels of +89.00 m (spillway gate sill) and +93.50 m (crest of the free-flow spillway). Additionally, an Early Warning System (EWS) with three alert levels (green, yellow, and red) has been established to anticipate emergency conditions. The best scenario was obtained under the closed-gate condition at RWL +89.00 m, achieving a 100% reduction in flood discharge for Q25 and maintaining dam safety against Q1000 (with a freeboard of 5.30 m). In contrast, the open-gate condition at RWL +93.50 m would result in downstream flooding, as the outflow discharge exceeds the bank full capacity; therefore, this scenario is not recommended for spillway gate operation. Overall, the study concludes that a well-planned gate operation system and an effective EWS can ensure dam safety and optimize its function as a flood control structure in the Tiu Suntuk watershed.